Personality traits influencing somatization symptoms and social inhibition in the elderly - Tinakon Wongpakaran (2018)
Purpose: Somatization is a common symptom among the elderly, and even though personality disorders have been found to be associated with somatization, personality traits have not yet been explored with regard to this symptom. The aim of this study is to investigate the relationship between personality traits and somatization, and social inhibition. Patients and methods: As part of a cross-sectional study of a community sample, 126 elderly Thais aged 60 years or over completed self-reporting questionnaires related to somatization and personality traits. Somatization was elicited from the somatization subscale when using the Symptom Checklist SCL-90 instrument. Personality traits were drawn from the 16 Personality Factor Questionnaire and social inhibition was identified when using the inventory of interpersonal problems. In addition, path analysis was used to establish the influence of personality traits on somatization and social inhibition. Results: Of the 126 participants, 51% were male, 55% were married, and 25% were retired. The average number of years in education was 7.6 (standard deviation =5.2). "Emotional stability" and "dominance" were found to have a direct effect on somatization, as were age and number of years in education, but not sex. Also, 35% of the total variance could be explained by the model, with excellent fit statistics. Dominance was found to have an indirect effect, via vigilance, on social inhibition, which was also influenced by number of years in education and emotional stability. Social inhibition was not found to have any effect on somatization, although hypothetically it should. Conclusion: "Emotional stability", "dominance", and "vigilance", as well as age and the number of years in education, were found to have an effect on somatization. Attention should be paid to these factors in the elderly with somatization. © 2014 Wongpakaran and Wongpakaran.